If it's not what You are looking for type in the equation solver your own equation and let us solve it.
=53V+3=
We move all terms to the left:
-(53V+3)=0
We get rid of parentheses
-53V-3=0
We move all terms containing V to the left, all other terms to the right
-53V=3
V=3/-53
V=-3/53
| -28=-4/9y | | 7-4x=5x+88 | | 26=5w-4 | | y=2•5+12 | | -17+20=-18+3b-5/2b | | y/8+66=73 | | 1/3n=27 | | x/3+3=57 | | -5x-9=7x-117 | | 12x2=9x+21 | | 100x+0.50=125x | | -8x+2(4x-3)=-6 | | 2=-2+x3 | | 14=36-x/2 | | 100x+0.50=125 | | -6x-4=4x-104 | | 6(v-88)=42 | | (3z/2)+(1/4)=7/8 | | 4(x+1)^4=68 | | K=1(20-7k) | | 6(t+2)=96 | | 10+4x-x=43 | | x-20+65=180 | | h-55/4=9 | | 5(n-93)=10 | | 80=-4(x+3)+12 | | -9=5x+7x-9 | | 144^x=1728 | | n+17.5=55 | | 12y+31=115 | | 10=b+35/6 | | 60=5x+5x |